Reis de Boi in the Noth of Espírito Santo - Vitor de Assis Zordan, Ana Rita; Vasconcelos Salume Zimerer, Fabiane (Guará Journal, 2015)
The study hereby presented reports the authors’ experience with the Project ‘Reis de Bois no ES’, which is part of a university program named ‘Entre Comunidades’ (PROEX/ UFES). Through a field research with interviews and photographic and audiovisual records, the mapping of the Reis de Boi groups in the North of Espírito Santo – the cities of São Mateus and Conceição da Barra – was made possible. The research comprises a thorough research on this specific cultural practice to give it a broader visibility via publications and presentations at conferences, seminars and photo exhibitions to recognize the Reis de Boi (it) as a means of preservation of the local culture.